Expanding the fluorescent toolkit: Blue fluorescent protein-expressing Plasmodium berghei for enhanced multiplex microscopy - Kodzo Atchou; Reto Caldelari; Magali Roques; Jacqueline Schmuckli-Maurer; Raphael Beyeler; Volker Heussler (PLoS ONE, 2025)
Fluorescent proteins are widely used as markers to differentiate genetically modified cells from their wild-type counterparts. In malaria research, the prevalent fluorescent markers include red fluorescent proteins (RFPs) and their derivatives, such as mCherry, along with green fluorescent proteins (GFPs) and their derivatives. Recognizing the need for additional fluorescent markers to facilitate multiplexed imaging, this study introduced parasite lines expressing blue fluorescent protein (BFP). These lines enable simultaneous microscopy studies of proteins tagged with GFP, RFP, or detected by fluorophore-labeled antibodies, enhancing the analysis of complex biological interactions. Expression of BFP throughout the parasite’s life cycle was driven by the robust Hsp70 promoter, ensuring stable, detectable protein levels suitable for fluorescent light analysis methods, including flow cytometry and fluorescent microscopy. We generated two Plasmodium berghei (P. berghei) lines expressing cytosolic BFP through double crossover homologous recombination targeting the silent 230p locus: eBFP2 (PbeBFP2) and mTagBFP2 (PbmTagBFP2). We compared these transgenic lines to established mCherry-expressing parasites PbmCherryHsp70 (PbmCherry) across their life cycles. The PbmTagBFP2 parasites exhibited fluorescence approximately 4.5 times brighter than the PbeBFP2 parasites in most life cycle stages. Both BFP-expressing lines developed normally through the entire parasite life cycle, offering a valuable expansion to the toolkit for studying Plasmodium biology at the host-pathogen interface.